(untitled) (Altre Modernità, 2017)
The essay discusses the making of Cecilia Rubino’s documentary “Remembering Shakespeare”. In collaboration with filmmaker Peter Lucas, she interviewed a wide range of people who live with Shakespeare’s words embedded in their daily lives.